SnO2-Bi2O3 and SnO2-Sb2O3 gas sensors obtained by soft chemical method - Montenegro Hernandez, Alejandra (2007)
In this work, SnO2-Bi2O3 and SnO2-Sb2O3 nanoparticles were obtained by using polymeric precursor method. Powders were characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM) and differential thermal analysis and thermogravimetric analysis (DTA/TGA). Thick films were deposited on alumina substrates on which electrodes have been previously deposited by sputtering. The electric response of thick films was measured under oxygen and carbon monoxide atmospheres. It was determined that bismuth addition improves the sensor response to the oxygen presence. On the other hand, antimony addition diminishes the sample resistance due to the possible replacement of Sn4+ by Sb5+.